2018
DOI: 10.1111/cas.13801
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MIFAS1 promotes gastric cancer cell proliferation and reduces apoptosis to upregulate NDUFA4

Abstract: Long non‐coding RNA MIF‐AS1 (lncMIF‐AS1) has been found to be upregulated in the tumor tissues of gastric cancer; however, its importance for the progression of gastric cancer remains unknown. Thus, the present study was designed to determine the role of the lncMIF‐AS1‐based signal transduction pathway in mediating the proliferation and apoptosis of gastric cancer cells. Differentially expressed lncRNAs and mRNAs were screened out using microarray analysis, based on the published data (GSE63288), and validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…[5][6][7] In addition, studies have found that some aberrant regulations between microRNA (miRNA) and mRNA have an important impact on the progression of gastric cancer. For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In addition, studies have found that some aberrant regulations between microRNA (miRNA) and mRNA have an important impact on the progression of gastric cancer. For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA.…”
mentioning
confidence: 99%
“…For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA. [5][6][7] In addition, studies have found that some aberrant regulations between microRNA (miRNA) and mRNA have an important impact on the progression of gastric cancer. 2,4,8 For the relationships of lncRNA-miRNA, although lncRNA and miRNA do not have the function of encoding proteins, the mutual regulations between lncRNA and miRNA can lead to abnormal expression of some signaling pathways and have an important influence on the growth, metastasis, metabolism, and apoptosis of gastric cancer cells.…”
mentioning
confidence: 99%
“…One study found that miR‐212‐5p may induce degradation or inhibit the expression of NDUFA4. Moreover, LncMIF‐AS1 was found to promote the expression of NDUFA4 in GC cells by binding miR‐212‐5p, and the recovered NDUFA4 strengthened the proliferative ability and prevented apoptosis of GC cells in vitro …”
Section: The Role Of Mir‐212 In Cancermentioning
confidence: 96%
“…Moreover, LncMIF-AS1 was found to promote the expression of NDUFA4 in GC cells by binding miR-212-5p, and the recovered NDUFA4 strengthened the proliferative ability and prevented apoptosis of GC cells in vitro. 31…”
Section: -5p Inhibited the Progression Of Rcc Cells Via Interactiomentioning
confidence: 99%
“…In silico analysis speculates that SNHG3 can function by sponging miR-186-5p. In gastric cancer tissues, expression levels of lncRNA MIF-AS1 ( lncMIF-AS1 ) and complex IV subunit NADH dehydrogenase1 alpha subcomplex 4 (NDUFA4) are higher compared with those in non-cancerous tissues ( 72 ). Mechanistically, lncMIF-AS1 sponges miR-212-5p to activate NDUFA4 expression.…”
Section: Oxphos With Lncrnamentioning
confidence: 99%